Hermeneutika Al-Qur’an Kontekstual: Metode Menafsirkan Al-Qur’an Abdullah Saeed - Hatib Rachmawan (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2013)
Quranic exegesis has a special place in the development of Islamic intellectual tradition and civilization at large. As the main source of Islamic teaching, for centuries Muslims have attempted to understand the various meanings of the Qur’an in order to be in line with the current needs of the society through the process of contextualization. In this article, the author presents and explains the way in which Abdullah Saeed, a professor in Islamic studies from the the University of Melbourne, Australia, contextualize the meaning of the Quran. In particular, this article analyzes some methodological aspects proposed by Saeed in the qontextualization of the Qur’an: 1) identifying the world of the text; 2) analyzing text critically; 3) connecting the text to the early Islamic community as the first receivers; and 4) relating the text to the current needs of society. Keywords: Quranic exegesis, Abdullah Saeed, tafsir methodology, contextualization.